Recycle the Fabric, Rebrand the Image: Strategi Cyber Public Relations UNIQLO dalam Membangun Citra Keberlanjutan melalui LifeWear - Riyantie, Mayang; Silitonga, Cindy Aulia; Putri, Jenisa Amalia (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The rapid development of digital technology has fundamentally transformed the role of public relations, particularly in the context of sustainability and brand communication. This study explores how Uniqlo’s Cyber Public Relations plays a strategic role in building a sustainable brand image through the LifeWear campaign on social media. Using a literature review approach based on ten academic journal sources, the research analyzes Uniqlo's digital communication strategies in conveying sustainability values to the public. Findings reveal that platforms such as Instagram and YouTube are strategically utilized to deliver visual, educational, and interactive narratives about eco-friendly products, RE.UNIQLO recycling programs, and endorsements by public figures. The LifeWear campaign is found to be effective in shaping positive consumer perceptions, enhancing brand equity, and fostering loyalty, especially when messages are delivered authentically and consistently. However, challenges such as the risk of greenwashing and low digital engagement remain significant barriers. Therefore, transparent, data-driven communication strategies that actively engage the public are essential. These findings highlight the importance of cyber public relations as a strategic bridge between corporate sustainability values and increasingly environmentally conscious consumer expectations in the digital era., inclusive, and responsive as an effort to build a fair, democratic, and civilized digital ecosystem.